10 Levels thoracic no-intrumented laminectomy for huge spontaneous spinal subdural hematoma removal. Report of the first case and literature review. (2015) - Visocchi, Massimiliano; La Rocca, Giuseppe; Signorelli, Francesco; Roselli, Romeo; Jun, Zhong; Spallone, A.
Highlights: In this article, reporting on the case of a huge 10 levels spontaneous spinal subdural hematoma treated with decompressive thoracic no-instrumented laminectomy in a 45-year-old woman with good neurological recovery, we would like to underline the importance of a timely surgical decompression as the mainstay option in the management of strongly symptomatic spontaneous idiopathic acute spinal subdural hematomas. To our knowledge, 10 levels thoracic laminectomy for a SSDH removal have never been described. We performed "conservative" laminectomy by sparing of articular processes with no need to posterior fixation also considering the intrinsic stability of thoracic chest. Abstract: Introduction: Spontaneous idiopathic acute spinal subdural hematoma (SSDH) is a rare cause of acute back pain followed by signs and symptoms of nerve root and/or spinal cord compression, frequently associated with coagulopathies, blood dyscrasias and arterio-venous malformations. Standard management includes non-operative treatment and timely (within 24 h) surgical decompression. Presentation of case: We report on the case of a huge 10 levels SSDH treated with decompressive thoracic no-instrumented laminectomy in a 45-year-old woman with good neurological recovery (from ASIA A to D). Discussion: Spontaneous SSDHs without detectable structural lesion or anticoagulant therapy are very rare. Among 26 cases documented the literature harbouring SSDHs, the thoracic spine was found to be the preferred site, and the compression was usually extending over several vertebral levels. Nonoperative treatment for SSDH may be justified in presence of minimal neurologic deficits, otherwise, early decompressive laminectomy along with evacuation of hematoma are considered the treatment of choice in presence of major deficits. Conclusion: To our knowledge, the present case is the most extensive laminectomy for a SSDH removal never described before. No postoperative instability occurs in 10 levels thoracic laminectomy in case the articular processes are spared. When major neurological deficits are documented, early decompressive laminectomy with evacuation of hematoma should be considered the best treatment for SSDH.